Knowledge, Attitudes, and Practices Regarding Teledentistry Among Dentists in Jakarta During the Coronavirus Disease (Covid-19) Pandemic: A Cross-Sectional Study - Septiviany Kun Prasidhati; Atik Ramadhani; Febriana Setiawati (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess factors associated with knowledge, attitudes, and practices (KAP) related to teledentistry among dentists in Jakarta during the COVID-19 pandemic. Material and Methods: This cross-sectional study used a self-administered online questionnaire with a purposive sampling technique. Survey items comprised knowledge of, attitude toward, the practice of, and barriers to teledentistry. The Chi-square, Mann-Whitney, and Spearman correlation tests were used to determine factors associated with KAP of teledentistry. Results: A total of 183 dentists in Jakarta completed the questionnaire. The findings showed that 95.6% of the surveyed dentists had good knowledge, 83.1% expressed positive attitudes, and 60.7% practiced teledentistry during the COVID-19 pandemic. Most participants (86.3%) expressed a willingness to practice teledentistry in the future. The three most significant barriers that obstruct dentists from practicing teledentistry are patient compliance and satisfaction regarding the dentist's physical presence, a low population education level, and a lack of technological infrastructure. A statistically significant relationship was found between teledentistry practice and age, marital status, working experience, and training regarding teledentistry. A positive correlation was found between knowledge of and attitude toward teledentistry. Conclusion: Dentists in Jakarta have a high understanding of, positive attitudes toward, and good practices for teledentistry. Factors related to teledentistry practice were age, marital status, work experience, and training experience in the last two years.